Ammonia Storage by Reversible Host–Guest Site Exchange in a Robust Metal–Organic Framework. Issue 45 (1st October 2018) - Godfrey, Harry G. W.; da Silva, Ivan; Briggs, Lydia; Carter, Joseph H.; Morris, Christopher G.; Savage, Mathew; Easun, Timothy L.; Manuel, Pascal; Murray, Claire A.; Tang, Chiu C.; Frogley, Mark D.; Cinque, Gianfelice; et al.
Abstract: MFM‐300(Al) shows reversible uptake of NH3 (15.7 mmol g −1 at 273 K and 1.0 bar) over 50 cycles with an exceptional packing density of 0.62 g cm −3 at 293 K. In situ neutron powder diffraction and synchrotron FTIR micro‐spectroscopy on ND3 @MFM‐300(Al) confirms reversible H/D site exchange between the adsorbent and adsorbate, representing a new type of adsorption interaction. Abstract : High storage capacity : MFM‐300(Al) shows reversible uptake of NH3 over 50 cycles with an exceptional packing density of 0.62 g cm −3 at 293 K. Neutron diffraction and FTIR micro‐spectroscopy confirm reversible H/D site exchange between the adsorbent and adsorbate, representing a new type of adsorption interaction.